Road traffic noise from a stopping line - Makarewicz, R.; Kokowski, P. (Archives of Acoustics, 2002)
A simple method, requiring simultaneous noise measurements at three positions is presented for the prediction of the equivalent continuous sound level, LAeqT, of road traffic noise generated at the stopping line. Geometrical spreading of noise is affected by reflection from the hard ground surface. This method can be applied when noise is produced by vehicles of one category, the traffic streams in both directions are almost identical, and the perpendicular distance between the road axis and the receiver exceeds the road width.